Reconfigurable Random Forest Implementation on FPGA - Raeisi Nafchi, Masood

Data Analytics for Predictive Maintenance of Time Series Data - Yadalam Murali Kumar, Nihal

On Guaranteeing Schedulability of Periodic Real-time Hardware Tasks under ReconOS64 - Clausing, Lennart; Guetattfi, Zakarya; Kaufmann, Paul; Lienen, Christian; Platzner, Marco (Proceedings of the 19th International Symposium on Applied Reconfigurable Computing (ARC))

On-The-Fly Computing -- Individualized IT-services in dynamic markets - Haake, Claus-Jochen; Meyer auf der Heide, Friedhelm; Platzner, Marco; Wachsmuth, Henning; Wehrheim, Heike
In the proposal for our CRC in 2011, we formulated a vision of markets for IT services that describes an approach to the provision of such services that was novel at that time and, to a large extent, remains so today: „Our vision of on-the-fly computing is that of IT services individually and automatically configured and brought to execution from flexibly combinable services traded on markets. At the same time, we aim at organizing markets whose participants maintain a lively market of services through appropriate entrepreneurial actions.“ Over the last 12 years, we have developed methods and techniques to address problems critical to the convenient, efficient, and secure use of on-the-fly computing. Among other things, we have made the description of services more convenient by allowing natural language input, increased the quality of configured services through (natural language) interaction and more efficient configuration processes and analysis procedures, made the quality of (the products of) providers in the marketplace transparent through reputation systems, and increased the resource efficiency of execution through reconfigurable heterogeneous computing nodes and an integrated treatment of service description and configuration. We have also developed network infrastructures that have a high degree of adaptivity, scalability, efficiency, and reliability, and provide cryptographic guarantees of anonymity and security for market participants and their products and services. To demonstrate the pervasiveness of the OTF computing approach, we have implemented a proof-of-concept for OTF computing that can run typical scenarios of an OTF market. We illustrated the approach using a cutting-edge application scenario – automated machine learning (AutoML). Finally, we have been pushing our work for the perpetuation of On-The-Fly Computing beyond the SFB and sharing the expertise gained in the SFB in events with industry partners as well as transfer projects. This work required a broad spectrum of expertise. Computer scientists and economists with research interests such as computer networks and distributed algorithms, security and cryptography, software engineering and verification, configuration and machine learning, computer engineering and HPC, microeconomics and game theory, business informatics and management have successfully collaborated here.

Flexible Industrial Analytics on Reconfigurable Systems-On-Chip - Boschmann, Alexander; Clausing, Lennart; Jentzsch, Felix; Ghasemzadeh Mohammadi, Hassan; Platzner, Marco (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

ReconOS64: A Hardware Operating System for Modern Platform FPGAs with 64-Bit Support - Clausing, Lennart; Platzner, Marco (2022 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW))

FreeRTOS on a MicroBlaze Soft-Core Processor with Hardware Accelerators - Tcheussi Ngayap, Vanessa Ingrid

Dealing With Pre-Processing And Feature Extraction Of Time-Series Data In Predictive Maintenance - Manjunatha, Suraj

Analysis of Time-Series Classification in Conditional Monitoring Systems - Kaur , Parvinder

ReconOS64: High-Performance Embedded Computing for Industrial Analytics on a Reconfigurable System-on-Chip - Clausing, Lennart (Proceedings of the 11th International Symposium on Highly Efficient Accelerators and Reconfigurable Technologies)